Korelasi Penguasaan Mata Pelajaran Bahasa Arab Dan Al-Qur’an Hadits - Nurmawaddah, Andi; Minabari, Khalid Hasan; Aswad, Faizah (Peneliti.net, 2024)
The purpose of this study was to determine the correlation between the mastery of Arabic and Al-Qur'an Hadith subjects in class VIII students of MTs Negeri 1 Tidore. The type of research used was a correlational research or relationship research with a quantitative approach method. Data collection techniques used were observation, questionnaires and documentation. This study has two variables, so the data analysis used was a single correlation technique using the Product Moment correlation coefficient technique formula. The results of the study showed that there was a significant relationship between mastery of Arabic and mastery of Al-Qur'an Hadith subjects. This was evidenced by the correlation coefficient value of 1.574 which can be interpreted that the value was in the interval of 0.80 - 1,000. Therefore, it can be concluded that the correlation between variables X and Y was high.